Perjanjian Terapeutik: Problematika dan Pelaksanaan di Rumah Sakit Umum Ir. Soekarno Provinsi Kepulauan Bangka Belitung - Salfutra, Reko Dwi; Agustian, rio Armanda; yokotani, yokotani (Fakultas Hukum Universitas Bangka Belitung, 2024)
A therapeutic agreement is a contractual relationship between a doctor and a patient. As a legal act, a therapeutic agreement carries legal consequences when the parties neglect or do not perform their obligations. In practice, often civil lawsuit cases are filed by a patient against a doctor as a result of non-performance of the therapeutic agreement. This study aims to identify and determine the legal problems in the implementation of therapeutic agreements between doctors and patients at Ir. Soekarno Hospital, Bangka Belitung. Based on these objectives, academically the results of this research are expected to be used as a starting point in legal research related to the implementation of therapeutic agreements between doctors and patients, and practically the results of this research are expected to be used as input in legal research on the implementation of therapeutic agreements between doctors and patients. This research uses socio legal research methods